Use of pre‐clinical surgically induced models to understand biomechanical and biological consequences of PTOA development. Issue 3 (2nd March 2017) - Barton, Kristen I.; Shekarforoush, Mehdi; Heard, Bryan J.; Sevick, John L.; Vakil, Paria; Atarod, Mohammad; Martin, Ryan; Achari, Yamini; Hart, David A.; Frank, Cyril B.; Shrive, Nigel G.
ABSTRACT: Post‐traumatic osteoarthritis (PTOA) development is often observed following traumatic knee injuries involving key stabilising structures such as the cruciate ligaments or the menisci. Both biomechanical and biological alterations that follow knee injuries have been implicated in PTOA development, although it has not been possible to differentiate clearly between the two causal factors. This review critically examines the outcomes from pre‐clinical lapine and ovine injury models arising in the authors' laboratories and differing in severity of PTOA development and progression. Specifically, we focus on how varying severity of knee injuries influence the subsequent alterations in kinematics, kinetics, and biological outcomes. The immediate impact of injury on the lubrication capacity of the joint is examined in the context of its influence on biomechanical alterations, thus linking the biological changes to abnormal kinematics, leading to a focus on the potential areas for interventions to inhibit or prevent development of the disease. We believe that PTOA results from altered cartilage surface interactions where biological and biomechanical factors intersect, and mitigating acute joint inflammation may be critical to prolonging PTOA development. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:454–465, 2017.